An Exploratory Study of Knowledge, Attitude and Practices of Rural Adolescent Girls and Life Challenges Faced Amid COVID-19 - Singh, Ritu; Mehra, Manisha; Bisht, Niharika (Indian Journal of Extension Education, 2021)
From a psychopathological viewpoint, COVID-19 is a relatively new form of stressor. COVID-19 and its relatedÂ containment measures namely lockdown, social distancing, and self-isolation are leading to increased loneliness and reduced social interactions having detrimental impact on psychosocial and mental health of generalÂ population especially adolescents. Spreading a large amount of uncontrolled news very rapidly with the risk of fake news running faster than the virus itself, and created uncertainties, worries and serious toll on theÂ mental health of adolescents especially rural girls due to the limited access to reliable information in villages and lack of formal professional help groups for resolving their other general crisis amid COVID-19. Hence, anÂ empirical research was undertaken to analyze the existing knowledge, attitude and practices (KAP) of rural adolescent girls pertaining to COVID-19 and their other life concerns amid COVID. A total of 187 adolescentÂ girls with access to smartphones were purposively selected from seven villages of Distt. U.S. Nagar and Nainital in Uttarakhand. Self structured questionnaire was developed to assess KAP pertaining to COVID-19 and informal talks were carried out to discuss their personal/familial/school issues amid COVID through telephonic call. Majority of rural girls were found to have moderate level of knowledge and were reported to have aÂ neutral attitude towards health seeking and preventive behaviour. Nearly half of the respondents were reported to be following inappropriate practices and had few personal/familial/school related issues which needed immediate attention and help. Telecounseling came as a boon for rural girls amid COVID-19. Post telecounseling, girls depicted notable improvement in KAP on COVID-19 and better mental health due to getting an authentic and reliable ear for hearing and assistance in finding solutions to their personal/familial or school related issues.